Why Would You Get THAT Done?! Stigma Experiences of Women with Piercings and Tattoos Attending Postsecondary Schools - Martin, Cayla R.; Cairns, Sharon L. (Canadian Journal of Counselling and Psychotherapy, 2015)
Research in the area of piercings and tattoos has indicated the existence of commonly held negative stereotypes and assumptions (stigmas) concerning these body practices. These stigmas have been shown to impact the hireability of those with body modification (BoM). In order to understand the experiences of women with piercings and tattoos who are entering the professional workforce, the first author interviewed 8 women attending postsecondary education between November 2011 and April 2012. Through analysis using a hermeneutic phenomenological approach, with a focus on experiences with work, friends, and family, 8 main themes emerged. Interpreting the data showed that, despite the increasing number of people with BoM, postsecondary women are still experiencing and/or anticipating workplace and familial stigma.